STUDENTS’ DIFFICULTIES IN LISTENING AND UNDERSTANDING SPEECH - Yunie Amalia Rakhmyta (Jurnal As-Salam, 2019)
Communication is the most important thing in human life. It was given to construct the best interaction between people. From the initial observation, most students have difficulties in understanding what they have listened to. The purpose of this research is to find out the most difficulties faced by students at second-semester unit B English department STAIN Gajah Putih Takengon academic year of 2017/2018. The methodology is descriptive method with qualitative approach. The techniques of collecting data are observation, test, interview, and documentation. Eventually, in finding describe some difficulties faced by the students in understanding the speech. The students do not gain satisfactory scores, low motivation in listening, lacked vocabularies and grammar obstacles. Most of all, the most difficulties is the speed. Students felt easier when listen to the slower speech rather than normal or faster speed. It is due to pronunciation style and intonation.